A Fine-Tuned Lipophilicity/Hydrophilicity Ratio Governs Antibacterial Potency and Selectivity of Bifurcated Halogen Bond-Forming NBTIs - Anja Kolarič; Maja Kokot; Martina Hrast; Matjaž Weiss; Irena Zdovc; Jurij Trontelj; Simon Žakelj; Marko Anderluh; Nikola Minovski (MDPI AG, 2021)
Herein, we report the design of a focused library of novel bacterial topoisomerase inhibitors (NBTIs) based on innovative mainly monocyclic right-hand side fragments active against DNA gyrase and Topo IV. They exhibit a very potent and wide range of antibacterial activity, even against some of the most concerning hard-to-treat pathogens for which new antibacterials are urgently needed, as reported by the WHO and CDC. NBTIs enzyme activity and whole cell potency seems to depend on the fine-tuned lipophilicity/hydrophilicity ratio that governs the permeability of those compounds through the bacterial membranes. Lipophilicity of NBTIs is apparently optimal for passing through the membrane of Gram-positive bacteria, but the higher, although not excessive lipophilicity and suitable hydrophilicity seems to determine the passage through Gram-negative bacterial membranes. However, due to the considerable hERG inhibition, which is still at least two orders of magnitude away from MICs, continued optimization is required to realize their full potential.